58. Cost-Effectiveness of Emerging Antibiotic Strategies for the Treatment of Drug-Use Associated Infective Endocarditis. (4th December 2021) - Adams, Joella W; Savinkina, Alexandra; Gai, Mam Jarra; Hill, Allison; Hudspeth, James; Jawa, Raagini; Kimmel, Simeon D; Marks, Laura; Linas, Benjamin P; Barocas, Joshua
Abstract: Background: Drug use-associated infective endocarditis (DUA-IE) is typically treated with 4-6 weeks of in hospital intravenous antibiotics (IVA). Outpatient parenteral antimicrobial therapy (OPAT) and partial oral antibiotics (PO) may be as effective as IVA, though long-term outcomes and costs remain unknown. We evaluated the clinical outcomes and cost-effectiveness of four antibiotic treatment strategies for DUA-IE. Methods: We used a validated microsimulation model to compare: 1) 4-6 weeks of inpatient IVA along with opioid detoxification, status quo (SQ); 2) 4-6 weeks of inpatient IVA along with inpatient addiction care services (ACS) which offers medications for opioid use disorder ( SQ with ACS ); 3) 3 weeks of inpatient IVA with ACS followed by OPAT ( OPAT ); and 4) 3 weeks of IVA with ACS followed by PO antibiotics ( PO ). We derived model inputs from clinical trials and observational cohorts. All patients were eligible for either in-home or post-acute care OPAT. Outcomes included life years (LYs), discounted costs, incremental cost-effectiveness ratios (ICERs), proportion of DUA-IE cured, and mortality attributable to DUA-IE. Costs (&US) were annually discounted at 3%. We performed probabilistic sensitivity analyses (PSA) to address uncertainty. Results: The SQ scenario resulted in 18.64 LY at a cost of &416, 800/person with 77.4% hospitalized DUA-IE patients cured and 5% of deaths in the population were attributable to DUA-IE. Life expectancy was extended by each strategy: 0.017y in SQ with ACS, 0.011 in OPAT, and 0.024 in PO . The PO strategy provided the highest cure rate (80.2%), compared to 77.9% in SQ with ACS and 78.5% in OPAT and X in SQ . OPAT was the least expensive strategy at &412, 300/person, Compared to OPAT, PO had an ICER of &141, 500/LY. Both SQ strategies provided worse clinical outcomes for money invested than either OPAT or PO (dominated). All scenarios decreased deaths attributable to DUA-IE compared to SQ . Findings were robust in PSA. Table 1 Selected cost and clinical outcomes comparing treatment strategies for drug-use associated infective endocarditis including the status quo, status quo with addiction care services, outpatient parenteral antimicrobial therapy, and partial oral antibiotics. Conclusion: Treating DUA-IE with OPAT along with ACS increases the number of people completing treatment, decreases DUA-IE mortality, and is cost-saving compared to the status quo. The PO strategy also improves clinical outcomes, but may not be cost-effective at the willingness-to-pay threshold of &100, 000. Disclosures: Simeon D. Kimmel, MD, MA, Abt Associates for a Massachusetts Department of Public Health project to improve access to medications for opioid use disorder in nursing facilities (Consultant)